Atlas of challenges and opportunities in European neighbourhoods : stemming from the ESPON "ITAN" project (Integrated Territorial Analysis of the Neighbourhoods) /: stemming from the ESPON "ITAN" project (Integrated Territorial Analysis of the Neighbourhoods). ([2016]) - Beckouche, Pierre, 1957-
No abstract available